The « Cooperative Wage Study » and the Canadian Steelworkers - Bean, Ronald (Relations industrielles / Industrial Relations, 1964)
SummaryIn contrast to a wealth of information relating to the techniques of implementing a fob evaluation programme relatively little attention has been given to the industrial relations aspects of such a scheme or to conditions necessary for securing union participation in it. In this paper it is our intention to analyse the CWS joint union-management job evaluation programme adopted in the Canadian steel industry from the standpoint of union objectives in pressing for its installation, collective bargaining aspects of the evaluation and internal union membership reactions. At the same time it is hoped to throw more light upon the wage policies and practices of the United Steelworkers — usually recognized as the largest and most powerful industrial union in Canada, about which little systematic knowledge at present exists.